Psychometric Analysis of the Ryff’s Psychological Well-Being Scales in Students of Four Mexican Universities - Balcázar Nava, Patricia (2018)
The objective of this research was to study the psychometric properties of the Ryff’s Psychological Well-Being Scales in the version of 39 items (Díaz et al., 2006) with samples from four Mexican universities. First, an exploratory factorial analysis was performed with 754 university students, testing different models according to the literature; the model with the best fit was the one that grouped the 31 items in three factors: Tendency to self-actualization, interpersonal and intrapersonal relations and Autonomy, with a total internal reliability of α = .77. In the second phase, we worked with 753 participants, with whom we performed a confirmatory analysis of which we obtained goodness of fit indices indicating a good model according to the criteria proposed by Hu and Bentler (1999). The factor loadings of the items were between .35 and .81, and the internal reliability of the test was α = .73. The findings confirm what other authors have concluded in this respect, that the hexa dimensional structure of the original model is not replicated.